Tunable electrical properties of multilayer HfSe2 field effect transistors by oxygen plasma treatment. Issue 4 (11th January 2017) - Kang, Moonshik; Rathi, Servin; Lee, Inyeal; Li, Lijun; Khan, Muhammad Atif; Lim, Dongsuk; Lee, Yoontae; Park, Jinwoo; Yun, Sun Jin; Youn, Doo-Hyeb; Jun, Chungsam; Kim, Gil-Ho
Abstract : HfSe2 field effect transistors are systematically studied in order to selectively tune their electrical properties by optimizing layer thickness and oxygen plasma treatment. Abstract : HfSe2 field effect transistors are systematically studied in order to selectively tune their electrical properties by optimizing layer thickness and oxygen plasma treatment. The optimized plasma-treated HfSe2 field effect transistors showed a high on/off ratio improvement of four orders of magnitude, from 27 to 10 5, a field effect mobility increase from 2.16 to 3.04 cm 2 V −1 s −1, a subthreshold swing improvement from 30.6 to 4.8 V dec −1, and a positive threshold voltage shift between depletion mode and enhancement mode, from −7.02 to 11.5 V. The plasma-treated HfSe2 photodetector also demonstrates a reasonable photoresponsivity from the visible to the near-infrared region of light.